Readiness for practice: The views of New Zealand senior nursing students. (July 2019) - Jamieson, Isabel; Sims, Deborah; Basu, Arindam; Pugh, Kate
Abstract: The concept of 'readiness to practice' of nursing students is not well understood even though being 'ready for practice' is the focus of undergraduate programs. The aim of this study was to critically explore senior student's views about their readiness to practice as a registered nurse. This study was undertaken in a school of nursing in the South Island of New Zealand. The participants included all senior nursing students assigned to their final clinical practicum from five cohorts across two and half years. The response rate for the survey across five cohorts was 46% (n = 245). The majority of students were New Zealand European females aged 30 years or younger. Students felt they were confident with their professional responsibilities and considered that they had prepared well for the profession. They agreed that they were confident with their communication skills. Areas of concern were; caring for a dying patient and caring for more than four patients at one time. This study suggests that senior nursing students feel they are work ready.